Plasmodium vivax infection compromises reticulocyte stability - Martha A. Clark (Nature Portfolio, 2021)
During Plasmodium intra-erythrocytic developmental, parasites compromise the structural integrity of host red-blood cells. Here, Clark et al. develop a flow cytometric osmotic stability assay to show that P. vivax infection destabilizes host reticulocytes, which are less stable than P. falciparum-infected normocytes.